RT-PCR of alcohol dehydrogenase genes from root and leaf sections of sago palm - Mohamad Shahril, Dahrawi Edrus. (Universiti Malaysia Sarawak (UNIMAS), 2007)
Plants have a remarkable ability to cope with different environmental stress through physiological and metabolic changes that are mostly induced by alterations of gene expression. Alcohol dehydrogenase (Adh) gene which encodes for enzymes of ethanolic fermentation were one of the genes involved in stress response. In this research, Adh genes which involved in anaerobic stress response in sago palm was attempted to be isolated via RT -PCR teehnique. CTAB and urea method was used to isolate total RNA from root and leaf sections of sago palm, however only CTAB method succeeded in isolating the total RNA. The isolation of Adh genes from both root and leaf sections of sago palm failed after several attempts. Therefore, the firststrand eDNA was analyzed and proven not to be the factor contributing to the failure. Other potential factors which cause the failure such as the plant samples and the primers used were discussed.